Core Folkbiological Concepts: New Evidence from Wichí Children and Adults - Taverna Loza, Andrea Sabina (2012)
We examine two core folk-biological concepts (e.g., ANIMATE, LIVING THING ) in adults and children from the Wichí community, an indigenous group of Amerindians living in the Chaco forest in north Argentina. We provide an overview of the Wichí community, describing in brief their interaction with objects and events in the natural world, and the naming systems they use to describe key folkbiological concepts. We then report the results of two behavioral studies, each designed to deepen our understanding of the acquisition of the fundamental folkbiological concepts ANIMATE and LIVING THING in Wichí adults and children. These results converge well with evidence from other communities. Wichí children and adults appreciate these fundamental concepts; both are strongly aligned with the Wichí community-wide belief systems. This work underscores the importance of considering cultural and linguistic factors in studying the acquisition of fundamental concepts about the biological world.